ANALISIS EFISIENSI DAYA LISTRIK PADAPROTOYPE PLTMH ALIRAN ANAK SUNGTUKAD SUNGI BANJAR GANTER DESA ABIAN TUWUNG - Panduwinata, K Satria; Indra Partha, C G; Janardana, I G N (Jurnal SPEKTRUM; Vol 11 No 4 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i04.p4, 2024)
This study aims to determine the efficiency of the electrical power generated from the Micro hydro Power Plant (MHP) prototype on the flow of tributaries of the tukad sungi Banjar Ganter Abian Tuwung Village. The efficiency obtained can be used as a parameter to determine how much the available hydraulic power potential can be utilized into electrical power. This research uses a quantitative analysis method which involves direct measurement of operational parameters such as water discharge, water fall height (head), electric voltage and electric current generated in the MHP prototype. Measurement of the electrical power generated by the MHP prototype produces different efficiencies according to the variation in the number of loads used, the highest efficiency of 7.75% is obtained when measuring using a load in the form of 6 12V 40W DC LED lights. The efficiency obtained is relatively small, this is because the electric power generated is only 37.54W while the available hydraulic power is 484.12W. The low electrical power generated is due to deviations in the specifications of the load used, so that the power generated does not match the power specifications listed on the load used.